Extensor Mechanism Disruption in Knee Dislocation - O'Malley, Michael; Reardon, Patrick; Pareek, Ayoosh; Krych, Aaron; Levy, Bruce A.; Stuart, Michael J. (The Journal of Knee Surgery, 2016)
Disruption of the knee extensor mechanism is a challenging injury with no clear consensus on optimal treatment. Although rare in the setting of knee dislocations, these injuries should not be overlooked. Acute, complete rupture of either the quadriceps or patellar tendon necessitates primary repair with or without augmentation. Surgical management may also be required in the setting of a partial tear if a significant extensor lag is present or nonoperative treatment has failed. Tendon augmentation is used during primary repair if the native tissue is inadequate or after a failed primary repair. The purpose of this study is to evaluate extensor mechanism disruption incidence, injury patterns, associated injuries, and surgical options, including a novel tendon augmentation technique. This procedure consists of primary patellar or quadriceps tendon repair with semitendinosus autograft augmentation utilizing a distal or proximal patellar socket. Advantages of repair with tendon augmentation include accelerated rehabilitation, decreased risk of patellar fracture from transverse or longitudinal bone tunnels, and less hardware complications. We recommend consideration of this technique for selected cases of acute extensor mechanism disruption in the setting of tibiofemoral dislocation.
Keywords: extensor mechanism disruption; knee dislocation